2020
DOI: 10.3389/fmed.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Observational Studies on the Association of Chronic Urticaria With Symptoms of Depression and Anxiety

Abstract: Background: Chronic urticaria (CU) is a frequently occurring skin condition associated with many psychological factors, but the effect size of associations varied in literature. Objectives: To perform a systematic review and meta-analysis on the associations of CU with the symptoms of depression and anxiety. Methods: According to a pre-specified protocol, we systematically searched articles published in PubMed, Web of Science, CNKI, and CQVIP databases between January 2000 and January 2019. Pooled estimates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
2
11
0
1
Order By: Relevance
“…In studies conducted during the COVID-19 pandemic, an increase has been reported in the incidence of diseases such as psoriasis and urticaria, and it has been stated that the increase in the adverse effects of the epidemic on the quality of life as well as social anxiety and stress may have caused the increase in these diseases. 4,[7][8][9][10] The results obtained in our study and the fact that these rates were increased during the period when the pandemic peaked in our country also support this. However, we believe that the decrease in the non-emergency admissions to outpatient clinics during the pandemic period when there were curfews, and the relative increase in admissions to outpatient clinics with diseases such as urticaria and psoriasis, which may cause emergency or stress, may have contributed to these changes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In studies conducted during the COVID-19 pandemic, an increase has been reported in the incidence of diseases such as psoriasis and urticaria, and it has been stated that the increase in the adverse effects of the epidemic on the quality of life as well as social anxiety and stress may have caused the increase in these diseases. 4,[7][8][9][10] The results obtained in our study and the fact that these rates were increased during the period when the pandemic peaked in our country also support this. However, we believe that the decrease in the non-emergency admissions to outpatient clinics during the pandemic period when there were curfews, and the relative increase in admissions to outpatient clinics with diseases such as urticaria and psoriasis, which may cause emergency or stress, may have contributed to these changes.…”
Section: Discussionsupporting
confidence: 86%
“…In studies conducted during the COVID‐19 pandemic, an increase has been reported in the incidence of diseases such as psoriasis and urticaria, and it has been stated that the increase in the adverse effects of the epidemic on the quality of life as well as social anxiety and stress may have caused the increase in these diseases 4,7‐10 . The results obtained in our study and the fact that these rates were increased during the period when the pandemic peaked in our country also support this.…”
Section: Discussionsupporting
confidence: 85%
“…5 In this study, we found a strong inverse correlation between the number of eases such as psoriasis and urticaria. [6][7][8][9] Although the percentage of hospital visits for dermatological diseases decreased after the pandemic arose, the percentage of scabies-related visits increased during the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the percentage of diseases such as irritant contact dermatitis, urticaria, psoriasis, and scabies increased. The increase in social anxiety and stress along with the negative impact on quality of life caused by the COVID‐19 pandemic may explain the proportional increase in diseases such as psoriasis and urticaria 6‐9 …”
Section: Discussionmentioning
confidence: 99%
“…The wide range of estimates of psychosocial factors among patients with CU was 16–96% ( 11 ). A recent meta-analysis found that CSU patients are six times more likely to suffer from anxiety and depression than healthy people ( 12 ). So, the psychiatric disorders associated with CSU should be taken seriously.…”
Section: Introductionmentioning
confidence: 99%